Onmyouji: Gesture-based virtual reality game - Weng Chou, Ka; Quek, Albert; Hong Yew, Hui (International Journal of Engineering and Technology, 2018)
With the emergence of Virtual Reality (VR), userâ€™s senses are taken into consideration in achieving a natural and intuitive human-computer interaction (HCI) as well for a more effective data interaction. The conventional keyboard and mouse interface and control methods of VR no longer sufficiently handles the richness of the information and facilitate intuitive user interaction in the virtual environment. There are alternative controllers such as motion controller used in the game, but this burden users for having them to hold a controller during gameplay. Hand gestures are a powerful tool for communication among humans. Hand gestures recognition has the potential to achieve the naturalness and intuitiveness for HCI. Here, we have proposed a VR game implemented a set of simple gestures with Leap Motion controller named Onmyouji. Onmyouji emphasizes on the VR experience provided with utilizing hand gestures to move and cast attack as the player control. A set of gestures are designed to fulfill the naturalness and intuitiveness of controls in the game. By qualitative user evaluation on a target interest group, most of the participants evaluated positively on the intuitive gestures and gameplay. For the overall game experience, all participants rated 4 and 5 out of 5 scores.Â Â